Extraction and Characterization of Nanocellulose from Wheat Straw: Facile Approach - Savita Sihag; Sheetal .; Jitender Pal; Monika Yadav (Journal of Water and Environmental Nanotechnology, 2022)
The environmental concern occurs due to the extreme use of synthetic materials that have been fortified to develop innovative, multifunctional, and sustainable materials using copious lignocellulosic biomass. In this present study, work was done on the extraction of nanocellulose from wheat straw, and found that wheat straw is an admirable source of cellulose. Chemical processes were used to isolate the cellulose and remove unwanted lignin and hemicellulose from wheat straw followed by sonication, cryo-crushing, and magnetic stirring to achieve nanocellulose. The observed amount of cellulose (36.1%), hemicellulose (30.3%), lignin (17%), and ash content (9.2%) of raw wheat straw. Structural, morphological, and thermal characterization were estimated from FTIR, XRD, FESEM, TEM, DSC, TGA, and AFM for the identification and characterization of extracted cellulose from wheat straw. FTIR showed that the peaks at wavelength 1430.50 cm-1 and 1638.41 cm-1 both show that cellulose is present in the extracted nanocellulose.  Extracted nanocellulose was crystalline and had a 68.96% Crystallinity Index. Morphological analysis, FESEM showed that the untreated wheat straw has an irregular porous structure but the extracted nanocellulose has a regular shape having straight fibers connected. TEM analysis showed that the extracted nanocellulose has a spherical shape structure connected, showing the regular shape, the obtained spherical shape regulates the nanocellulose for further applications. Thermal degradation was observed using TGA which shows that the nanocellulose decomposition was observed around 3600C. AFM determination shows a bell-shaped structure on a smooth surface with a particle height of 3.2 nm and the mean roughness of 110.4 nm was obtained from the extracted nanocellulose. Extracted nanocellulose has a particle size of 58.77 nm.